2019
DOI: 10.1088/1361-665x/ab3901
|View full text |Cite
|
Sign up to set email alerts
|

A self-powered electronic-skin for detecting CRP level in body fluid based on the piezoelectric-biosensing coupling effect of GaN nanowire

Abstract: A self-powered biosensing electronic-skin for real-time blood analysis has been presented based on the piezoelectric-biosensing coupling effect of GaN nanowire. The piezoelectric output generated by GaN nanowires can be regarded as both the power source to drive the device and the piezoelectric-biosensing signal for detecting C-reactive protein (CRP). The outputting voltage of the device immersing in the test solution is significantly affected by the CRP concentration, and the response is up to 78.2% against 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition, by injecting 0.6 mM uric acid solution at the site of the device, the output piezoelectric voltage decreases from ∼0.2 V to ∼0.05 V, illustrating the responsiveness of the device towards uric acid. To monitor the acute and chronic inflammation in real time, Lei et al 143 reported a 6 cm × 6 cm e-skin synthesised from GaN nanowire arrays; it performs sensing of CRP by modifying C-reactive protein antibodies on the surface of the nanowires. The output voltage of this device in pure water is 86.32 mV; when the CRP antigen concentration reaches 0.624 mg ml −1 it will decrease to 18.79 mV and the response at this point is 78.2%, and the sensitivity of this self-powered e-skin is about 0.030 mg ml −1 .…”
Section: Applications Of Self-powered Biosensorsmentioning
confidence: 99%
“…In addition, by injecting 0.6 mM uric acid solution at the site of the device, the output piezoelectric voltage decreases from ∼0.2 V to ∼0.05 V, illustrating the responsiveness of the device towards uric acid. To monitor the acute and chronic inflammation in real time, Lei et al 143 reported a 6 cm × 6 cm e-skin synthesised from GaN nanowire arrays; it performs sensing of CRP by modifying C-reactive protein antibodies on the surface of the nanowires. The output voltage of this device in pure water is 86.32 mV; when the CRP antigen concentration reaches 0.624 mg ml −1 it will decrease to 18.79 mV and the response at this point is 78.2%, and the sensitivity of this self-powered e-skin is about 0.030 mg ml −1 .…”
Section: Applications Of Self-powered Biosensorsmentioning
confidence: 99%
“…An important indicator of human health is the composition of body fluids. The large amount of mechanical energy generated by the human body can also be used to drive a self-powered body fluid sensor to collect body fluid data [31][32][33][34][35][36][37][38]. In addition to the real-time detection of body fluids by self-powered technology, the self-powered technology can be used to deliver drugs to the patient according to changes in the chemical com- [28].…”
Section: Self-powered Implantable Sensorsmentioning
confidence: 99%
“…Nanogenerators (NGs) can effectively harvest energy various low-frequency mechanical motions from the environment. NG-based self-powered sensors act as data collection units for traffic [3][4][5][6][7][8][9][10][11], meteorological environment [12][13][14][15][16][17][18][19][20][21], human movement [22][23][24][25][26][27], viscera [28][29][30], body fluid composition [31][32][33][34][35][36][37][38][39], biological nerve impulses [40], and gas sensors [18][19][20]. Self-powered sensors based on NGs can analyze objects from a new perspective.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10] Furthermore, as the wearable sweat sensor technology advances in its development, strategies such as the use of smart materials for self-powering will further enhance their functionality in the near future. [11][12][13] Among sweatbased wearable devices, electrochemical biosensors are considered most suitable for disease diagnosis and biological sample analysis, because they directly transduce the biochemical signals to faithfully quantifiable electrical outputs, are low in cost, and are easily integrable to portable wearable electronics due to miniaturization and higher sensitivity and signal-to-noise ratios. [14][15][16] In the currently available sweat monitors, however, the focus is narrowed down to a single biomarker level.…”
Section: Introductionmentioning
confidence: 99%